Sorcin links calcium signaling to vesicle trafficking, regulates Polo-like kinase 1 and is necessary for mitosis. - Vasiliki S Lalioti (Public Library of Science (PLoS), 2014)
Sorcin, a protein overexpressed in many multi-drug resistant cancers, dynamically localizes to distinct subcellular sites in 3T3-L1 fibroblasts during cell-cycle progression. During interphase sorcin is in the nucleus, in the plasma membrane, in endoplasmic reticulum (ER) cisternae, and in ER-derived vesicles localized along the microtubules. These vesicles are positive to RyR, SERCA, calreticulin and Rab10. At the beginning of mitosis, sorcin-containing vesicles associate with the mitotic spindle, and during telophase are concentrated in the cleavage furrow and, subsequently, in the midbody. Sorcin regulates dimensions and calcium load of the ER vesicles by inhibiting RYR and activating SERCA. Analysis of sorcin interactome reveals calcium-dependent interactions with many proteins, including Polo-like kinase 1 (PLK1), Aurora A and Aurora B kinases. Sorcin interacts physically with PLK1, is phosphorylated by PLK1 and induces PLK1 autophosphorylation, thereby regulating kinase activity. Knockdown of sorcin results in major defects in mitosis and cytokinesis, increase in the number of rounded polynucleated cells, blockage of cell progression in G2/M, apoptosis and cell death. Sorcin regulates calcium homeostasis and is necessary for the activation of mitosis and cytokinesis.